Marriage, the Law, and Samesex Unions - Gray, Christopher (Revue générale de droit, 1999)
This study argues against the contemporary project of acquiring the legal status of marriage for samesex unions. The preparatory normative approach identifies the religious wrong and the moral unacceptability of samesex sexual activity and liaisons. Legal norms are then superimposed to argue that, while criminalizing homosexual conduct is not now appropriate, the balance of public benefit weighs in favour of preventing samesex marriage, at least by not promoting it as giving it legal status would do. Most pointedly, this treatment is not excluded as a violation of rights, neither a right to freedom of association, nor a right to protection from discrimination, nor a right to equality.